Radial Fourier multipliers of L(p)(R(2)) - Carbery, Anthony (1984)
We give sufficient conditions (in terms of differentiability and growth properties) for a radial function to be an L(p)(R(2)) Fourier multiplier. These conditions are in the nature of best possible.